Telemedicine consultation «patient-doctor» in child psychiatry: methodology and practice - S P Morozov; M A Bebchuk; A V Vladzymyrskyy; O Z Khairetdinov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
Telepsychiatric assistance in the “doctor-patient” format is at the stage of formation and requires the solution of legal, organizational and methodological issues. The aim of the study was to substantiate the methodology of telemedicine consultations of patients (legal representatives) in child psychiatry. Material and methods. The analysis of the results of 1129 telemedicine consultations (TMK) in the «patient-doctor» format for 559 patients aged 2 to 18 years was carried out. Results. Remote consultations have been tested for the entire spectrum of mental disorders in childhood and adolescence. During the primary patient-doctor TMK, a number of serious regulatory and technical limitations were identified. Repeated TMK «patient — doctor» in child psychiatric practice are defined as the most optimal and safe. There was a significant increase in the number of repeated TMKs and the expansion of the specialties of consultants during the period of restrictive measures in connection with the COVID-19 pandemic. The assessment of the effectiveness of TMK was carried out by means of a sociological survey (questionnaire) of doctors and patients (legal representatives). Conclusion. A methodology has been developed for organizing and conducting telemedicine consultations for patients under the age of 18 (legal representatives) in the field of psychiatry. A survey of beneficiaries recorded their high readiness and satisfaction with remote counseling. A survey of medical workers revealed a positive trend in attitudes towards carrying out TMK. The negative dynamics of the opinions of specialists in connection with the increase in the level of workload indicates the need for further organizational, methodological and educational work on the use of telemedicine technologies.